Moodle e GeoGebra como apoio virtual ao ensino de trigonometria segundo a nova proposta curricular do estado de São Paulo - Aguiar, Anderson Luiz de (2011)
This work is the development, implementation and evaluation of a Virtual Learning Environment to support teaching trigonometry Curriculum Proposal according to the State of São Paulo, with strong use of dynamic geometry viewers. That proposal, implemented since 2008 with the name São Paulo Faz Escola, brings a series of actions to improve of education in face of national assessments of São Paulo, and the international quality indicators established by the Ministry of Education. The teaching material from these actions required a recycling of the practice, focusing on learning skills and abilities. Within this overall picture we develop teaching sequences with the use of ICT (Information and Communication Technologies) to show the student as the protagonist of the construction of knowledge. The implementation of the environment occurred in the first grade of Public Hight School, Newton Prado, during the 4th school grade of 2010 and had part of its five weekly classes held in the computer lab. We believe that these results will undoubtedly contribute to the improvement and development of basic education, especially math.